THE EFFECT OF JOB STRESS, WORKLOAD AND WORK ENVIRONMENT ON EMPLOYEE TURNOVER (CASE STUDY AT PT HASJRAT ABADI MANADO) - Ngantung, Gabriela R. (Sam Ratulangi University, 2015)
ABSTRACT The term â€œemployee turnoverâ€ is an important metric that is often central to organizationâ€™ workforce planning and strategy. The impact of turnover has received considerable attention by senior management, human resources professionals and industrial psychologists. It has proven to be one of the most costly and seemingly intractable human resource challenges confronting by several organizations globally. Organizations invest a lot on their employees in terms of induction and training, developing, maintaining and retaining them in their organization. The objective of this research is to identify the effect of job stress, workload, and work environment on employee turnover. In this research, the population refers to the employees of PT Hasjrat Abadi Manado with sample size as many as 50 respondents. The data are gathered from using questionnaires and used multiple regression analysis. Result showed that job stress, workload, and work environment have significant effect on employee turnover simultaneously and partially at PT Hasjrat Abadi Manado. Keywords: job stress, workload, work environment, employee turnover.